Docking Of Different Enzymes With Quercetin - Ng, Pei Ling; Wahab, Habibah A.; Adnan, Rohana (2003)
Flavonoids are a group of polyphenols that widely exists as colourful pigment for fruits,vegetables and herbs. Quercetin is one of the major components of flavonoids.